Understanding Policy Decisions - Dente, Bruno; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book proposes a model for understanding how innovative policy decisions are taken in complex political and organizational systems as well as the possible strategies that the promoter of the innovation can employ in order to maximize the probability of successful adoption and implementation. It presents a conceptual framework for the analysis of decisional situations in order to design the most appropriate strategies for overcoming conflict (e.g. of the NIMBY variety) and/or increasing the engagement of potentially interested actors. The book includes a template for decisional case studies, a protocol for the definition of a decisional strategy, and an exercise in decisional analysis.
Understanding Policy Decisions -- Models for Understanding Policy Decisions -- Who Decide? Actors and Their Resources -- What Is Decide? The Content of the Decision -- How to Decide? The Patterns of Interaction -- When and Where to Decide? the Decisional Context -- Taking Complex Decisions. What Are the Strategies? -- Studying Decisions.
Keywords: Economics; Statistics; Operations research; Economics/Management Science; Operation Research/Decision Theory; Statistics for Social Science, Behavorial Science, Education, Public Policy, and Law; Political Theory